Peran Serikat Pekerja Dalam Menjamin Kesejahteraan Karyawan di Indonesia - Abdullah, Nayla Putri; Amelia, Sabina Putri; Widiastiwi, Alisha Reva (Media Hukum Indonesia (MHI), 2024)
Trade unions are organizations created by workers to seek their rights and improve their welfare. Trade unions in Indonesia play a crucial role in protecting workers' rights and improving workers' welfare. However, in practice, there are various obstacles that hinder the effective role of trade unions in achieving this goal. The aim of this research is to analyze the role of trade unions in improving workers' welfare in Indonesia. This research uses a normative juridical approach by examining statutory regulations and related literature. As for the results of this research, we found that basically every worker has the right to have a trade union and of course this trade union has a very important role, especially in ensuring the welfare of workers as its members. In general, strong trade unions with visionary leadership, adequate resources, and support from the wider community can play an important role in improving the rights and welfare of their members. It is important to remember that labor unions are not the only parties playing a role in fighting for employee rights. The role of government and entrepreneurs is also very important in creating a conducive and fair work environment for all parties.